2020
DOI: 10.1111/jre.12775
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resveratrol on the progression of experimental periodontitis in an ovariectomized rat model of osteoporosis: Morphometric, immune‐enzymatic, and gene expression analysis

Abstract: Objective: This study aimed to determine the role of resveratrol (RESV) on the progression of experimental periodontitis (EP) in ovariectomy rats (OVT). Background: Estrogen deficiency is the main cause of osteoporosis and is related to higher periodontal attachment loss and reduction of alveolar bone. Zoledronate (ZLD) is an antiresorptive drug used to control osteoporosis but can lead to osteonecrosis of the jaw. RESV, a natural product, can reduce bone loss and control and prevent osteoporosis. Thus, this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Many studies have been conducted to elucidate the pathogenesis of MRONJ, and there are several reports on those related to periodontal and pulp diseases in rats [38][39][40][41][42][43][44][45][46][47][48]. Particularly, when a surgical procedure such as tooth extraction is performed in a state of chronic in ammation such as periodontitis, the incidence of MRONJ is high [38][39][40][41][42][43][44][45]. Although various hypotheses have been proposed regarding the pathogenesis of MRONJ, the mechanism related to macrophage activation is considered the most in uential [38].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted to elucidate the pathogenesis of MRONJ, and there are several reports on those related to periodontal and pulp diseases in rats [38][39][40][41][42][43][44][45][46][47][48]. Particularly, when a surgical procedure such as tooth extraction is performed in a state of chronic in ammation such as periodontitis, the incidence of MRONJ is high [38][39][40][41][42][43][44][45]. Although various hypotheses have been proposed regarding the pathogenesis of MRONJ, the mechanism related to macrophage activation is considered the most in uential [38].…”
Section: Discussionmentioning
confidence: 99%
“…Besides such effects, it also exerts favorable effects on osteoporosis in ovariectomized rats and mice, as summarized in Table 1 . Several studies have demonstrated that the oral administration of resveratrol in ovariectomized rodents mitigates estrogen deficiency-induced bone loss [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ], and with respect to its anti-osteoporotic mechanisms, it has been demonstrated that resveratrol not only promotes osteoblast differentiation but also suppresses osteoclast differentiation [ 22 , 24 , 28 ]. It has been proposed that microRNAs (miRNAs/miRs) play a pivotal role in estrogen deficiency-induced osteoporosis prevention.…”
Section: Resveratrolmentioning
confidence: 99%
“…Resveratrol suppresses the expression of miR 338 3p, which serves as a negative regulator of osteogenic differentiation in bone marrow stromal cells [ 29 ], and enhances the expression of miR-92b-3p, which inhibits osteoclast proliferation and stimulates osteoblast differentiation by suppressing the activity of the NADPH oxidase 4 (Nox4)/nuclear factor kappa B (NF-κB) signaling pathway [ 26 ]. Additionally, the administration of resveratrol to ovariectomized rats downregulates the expression of Nox enzymes, which are responsible for the production of ROS, resulting in the mitigation of estrogen deficiency-induced alveolar bone loss [ 27 ].…”
Section: Resveratrolmentioning
confidence: 99%
“…It was hypothesized that resveratrol (3,5,4′‐trihydroxystilbene), a plant‐derived polyphenol with antioxidant, antitumor, anti‐inflammatory, and antiresorptive effects (Bo et al, 2013), could be an interesting alternative to prevent MRONJ occurrence. Resveratrol (RES) can enhance bone repair, upregulation of bone remodeling, and downregulation of osteoclastogenic markers (Casarin et al, 2014; Franck et al, 2018; Molez et al, 2020; Pino et al, 2017; Wong et al, 2020). Additionally, RES can inhibit apoptosis (Kumar et al, 2015), directly affecting osteonecrosis control.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol (RES) can enhance bone repair, upregulation of bone remodeling, and downregulation of osteoclastogenic markers (Casarin et al, 2014;Franck et al, 2018;Molez et al, 2020;Pino et al, 2017;Wong et al, 2020). Additionally, RES can inhibit apoptosis (Kumar et al, 2015), directly affecting osteonecrosis control.…”
mentioning
confidence: 99%